Real-time imaging of photosynthetic oxygen evolution from spinach using LSI-based biosensor - Kasai, Shigenobu; Sugiura, Yamato; Prasad, Ankush; Inoue, Kumi Y; Sato, Teruya; Honmo, Tomohiro; Kumar, Aditya; Pospíšil, Pavel; Ino, Kosuke; Hashi, Yuka; Furubayashi, Yoko; Matsudaira, Masahki; et al. (Scientific reports, 2019)
The light-driven splitting of water to oxygen (O2) is catalyzed by a protein-bound tetra-manganese penta-oxygen calcium (Mn4O5Ca) cluster in Photosystem II. In the current study, we used a large-scale integration (LSI)-based amperometric sensor array system, designated Bio-LSI, to perform two-dimensional imaging of light-induced O2 evolution from spinach leaves. The employed Bio-LSI chip consists of 400 sensor electrodes with a pitch of 250 μm for fast electrochemical imaging. Spinach leaves were illuminated to varying intensities of white light (400-700 nm) which induced oxygen evolution and subsequent electrochemical images were collected using the Bio-LSI chip. Bio-LSI images clearly showed the dose-dependent effects of the light-induced oxygen release from spinach leaves which was then significantly suppressed in the presence of urea-type herbicide 3-(3,4-dichlorophenyl)-1,1-dimethylurea (DCMU). Our results clearly suggest that light-induced oxygen evolution can be monitored using the chip and suggesting that the Bio-LSI is a promising tool for real-time imaging. To the best of our knowledge, this report is the first to describe electrochemical imaging of light-induced O2 evolution using LSI-based amperometric sensors in plants.
Keywords: elektrochemické techniky; Oxygen; Photosynthesis; fotosyntéza; kyslík; Electrochemical Techniques; Spinacia oleracea; Biosensing Techniques; biosenzitivní techniky